Monitoring cementless femoral stem insertion by impact analyses: An in vitro study. (December 2018) - Tijou, Antoine; Rosi, Giuseppe; Vayron, Romain; Lomami, Hugues Albini; Hernigou, Philippe; Flouzat-Lachaniette, Charles-Henri; Haïat, Guillaume
Abstract: The primary stability of the femoral stem (FS) implant determines the surgical success of cementless hip arthroplasty. During the insertion, a compromise must be found for the number and energy of impacts that should be sufficiently large to obtain an adapted primary stability of the FS and not too high to decrease fracture risk. The aim of this study is to determine whether a hammer instrumented with a force sensor can be used to monitor the insertion of FS. Cementless FS of different sizes were impacted in four artificial femurs with an instrumented hammer, leading to 72 configurations. The impact number when the surgeon empirically felt that the FS was fully inserted was noted N surg . The insertion depth E was assessed using video motion tracking and the impact number N vid corresponding to the end of the insertion was estimated. For each impact, two indicators noted I and D were determined based on the analysis of the variation of the force as a function of time. The pull-out force F was significantly correlated with the indicator I (R 2 = 0.67). The variation of D was analyzed using a threshold to determine an impact number N d, which is shown to be closely related to N surg and N vid, with an average difference of around 0.2. This approach allows to determine i) the moment when the surgeon should stop the impaction procedure in order to obtain an optimal insertion of the FS and ii) the FS implant primary stability. This study paves the way towards the development of a decision support system to assist the surgeon in hip arthroplasty. Graphical abstract: Highlights: A method is proposed in order to monitor the insertion of femoral stem. The method is based on the impact analyses using an instrumented hammer. The insertion endpoint and the primary stability of the implant are assessed.